(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper we analyse the M/G/1 feedback queue under steady states conditions when catastrophe occur. The stationary probability of ‘n’ and zero customers sins the system are derived. The asymptotic behaviour of the model and the averages queues length are also obtained. The numerical example are provided to test the feasibility of the model.